Kemampuan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 20 Kupang Tahun Ajaran 2025/2026 - Delila Penna; Semuel H. Nitbani; Narantoputrayadi Makan Malay (Jurnal Lazuardi, 2026)
The focus of this research is on the "writing ability of descriptive texts of seventh-grade students at SMP Negeri 20 Kupang in the academic year 2025/2026." The aim of this study is to identify and analyze the descriptive text writing ability of seventh-grade students at SMP Negeri 20 Kupang in the academic year 2025/2026. The theory used is Constructivist Learning Theory. The method employed is Qualitative Descriptive Method. In this research, the author chose descriptive text material with the theme of school environment. Based on the analysis of 26 student worksheets from class VII-A writing descriptive texts according to the aspects of structure and linguistic rules, it was found successful because 24 students were able to write descriptive texts well, proven by a percentage of 92.30%, while 2 students, with a percentage of 7.69%, were not yet able. Based on the above analysis, the researcher concludes that the seventh-grade students of SMP Negeri 20 Kupang can be considered capable.